Capturing commemoration: Using mobile recordings within memory research. (May 2018) - Birdsall, Carolyn; Drozdzewski, Danielle
This paper details the contribution of mobile devices to capturing commemoration in action. It investigates the incorporation of audio and sound recording devices, observation, and note-taking into a mobile (auto)ethnographic research methodology, to research a large-scale commemorative event in Amsterdam, the Netherlands. On May 4, 2016, the sounds of a Silent March—through the streets of Amsterdam to Dam Square—were recorded and complemented by video grabs of the march's participants and onlookers. We discuss how the mixed method enabled a multilevel analysis across visual, textual, and aural layers of the commemorative atmosphere. Our visual data aided in our evaluation of the construction of collective spectacle, while the audio data necessitated that we venture into new analytic territory. Using Sonic Visualiser, we uncovered alternative methods of "reading" landscape by identifying different sound signatures in the acoustic environment. Together, this aural and visual representation of the May 4 events enabled the identification of spatial markers and the temporal unfolding of the Silent March and the national 2 minutes' silence in Amsterdam's Dam Square.